2015
DOI: 10.1002/jcph.501
|View full text |Cite
|
Sign up to set email alerts
|

Single‐dose evaluation of safety, tolerability and pharmacokinetics of newly formulated hydromorphone immediate‐release and hydrophilic matrix extended‐release tablets in healthy Japanese subjects without co‐administration of an opioid antagonist

Abstract: This single dose, open-label study investigated the safety, tolerability and pharmacokinetics of single oral doses of newly formulated immediate-release (IR) and hydrophilic matrix extended-release (ER) hydromorphone tablets in healthy Japanese subjects without co-administration of an opioid antagonist under fasting and fed conditions. Plasma and urinary concentrations of hydromorphone and metabolites were measured by liquid-chromatography tandem mass-spectroscopy. Following administration of the ER tablet, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Therefore, it was of interest to compare OF concentrations resulting from Substitol™ intake with those from patients prescribed hydromorphone. A pharmacokinetic study of single-dose hydromorphone showed maximal plasma concentrations in a very low ng/ml range, 24 in agreement with our results for OF concentrations in patients treated for pain with hydromorphone. The OF/serum ratio for hydromorphone has not been previously reported, and was found to be close to 1.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it was of interest to compare OF concentrations resulting from Substitol™ intake with those from patients prescribed hydromorphone. A pharmacokinetic study of single-dose hydromorphone showed maximal plasma concentrations in a very low ng/ml range, 24 in agreement with our results for OF concentrations in patients treated for pain with hydromorphone. The OF/serum ratio for hydromorphone has not been previously reported, and was found to be close to 1.…”
Section: Discussionsupporting
confidence: 92%
“…The primary objective of the study was to evaluate the safety, tolerability, and pharmacokinetics profiles following single doses of immediate-release and extended release (ER) hydromorphone tablets in healthy male Japanese subjects [19]. For miRNA measurement, blood samples were collected from a treatment group comprising six individuals administered with 6 mg of ER tablets of hydromorphone (Daiichi Sankyo Co., Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Measurements were performed on blood samples previously collected from two independent clinical studies, in which extended-release (ER) tablets of hydromorphone or oxycodone were administered to healthy male volunteers [19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…Hydrophilic matrix technology is a method for ER of drugs and has been widely used for oral controlled delivery of various drugs, including hydromorphone [10]. Given their hydrophilic nature, these polymers begin to swell upon contact with water, forming a gel layer.…”
Section: Introductionmentioning
confidence: 99%